2019
DOI: 10.1097/prs.0000000000005351
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Prescribing and Consumption Patterns following Outpatient Plastic Surgery Procedures

Abstract: Background: Opioid overprescribing is a nationwide problem contributing to the current epidemic. This study evaluated opioid consumption, physician prescribing, and patient satisfaction with pain control following outpatient plastic surgery procedures. Methods: Patients completed a questionnaire during their first postoperative visit. The authors queried about procedure type, quantity of opioids prescribed and consumed, days to opioid cessation, prescri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
54
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 23 publications
3
54
1
Order By: Relevance
“…A recent study showed that patients undergoing abdominoplasty and reduction mammoplasty consume the most quantity of opioids compared with patients undergoing outpatient plastic surgery procedures. 3 Although opioids are effective in pain control, they are also associated with an undesirable side effect profile, including dizziness, nausea, vomiting, pruritis, and respiratory depression. Another concerning aspect of opioid use is the potential to develop persistent opioid use.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that patients undergoing abdominoplasty and reduction mammoplasty consume the most quantity of opioids compared with patients undergoing outpatient plastic surgery procedures. 3 Although opioids are effective in pain control, they are also associated with an undesirable side effect profile, including dizziness, nausea, vomiting, pruritis, and respiratory depression. Another concerning aspect of opioid use is the potential to develop persistent opioid use.…”
Section: Introductionmentioning
confidence: 99%
“…14 Preoperative counseling has also been recommended to assess the patients’ expectation regarding pain and discomfort following a surgical procedure. 22,24 Preoperatively, there are multiple “red flags” that should alert the surgeon to the possibility that a known opioid-dependent patient may not manage postoperatively and may suffer adverse events, for example, an uncertain address or multiple addresses, no social support structures, a false or inconsistent history, 14 multiple doctors who are prescribing opioids, other comorbidities, 18 a complex psychiatric history, 14 verbal or physical abuse of staff, non-attendance at preoperative appointments, a history of increased opioid use after previous surgeries, 10 use of immediate release formulations, 18 or a history of illegal activity.…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral issues, such as patients demanding more pain medication, malingering, and desperation mentioned in the case report in the postoperative phase, are known to “also result from under medication in pain patients.” 42,43 Sometimes having a benchmark of how many opioids are usually necessary can assist in prescribing practices, for example, in outpatient plastic surgery: “reduction mammoplasty and abdominoplasty patients consumed the most opioids at 17 and 18.6 pills respectively.” 24 Data such as these can only serve as a guide, as patients’ individual needs may vary. 44…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abuse has previously been commented on in the obstetric [ 4 ], orthopedic [ 5 ], and otolaryngological [ 6 ] literature. Plastic surgeons, in particular, have been found to prescribe almost double the amount of opioids that patients who undergo outpatient procedures actually consume [ 7 ].…”
Section: Introductionmentioning
confidence: 99%